Spatial patterns of wild oysters in the Hawkesbury River, NSW, Australia - Summerhayes, Stephen A.; Kelaher, Brendan P.; Bishop, Melanie J. (Journal of Shellfish Research, 2009)
The native Sydney rock oyster, Saccostrea glomerata, is under increasing threat from QX disease, competition with nonnative Crassostrea gigas and coastal development. Knowledge of the distribution and population structure of S. glomerata and C. gigas is essential if oysters and their ecosystem services are to be successfully managed. We determined spatial patterns of abundance, condition, and size-structure of S. glomerata and C. gigas, across two key habitats, mangroves, and rocky shores of the Hawkesbury River, a highly modified estuary 50 km north of Sydney. Sampling of five sites per habitat, spanning a 15 km stretch of river, revealed abundant populations of S. glomerata, averaging 514 ± 185 m -2 , in mangroves and on rocky shores. The native oyster accounted for 99% of all oysters sampled, with C. gigas found only at two of the five sites sampled within each habitat. Overall, rocky shores supported over eight times the oyster cover as mangroves. Among rock sites, live oyster cover and condition generally decreased with distance upstream. Although, at present, the Hawkesbury River estuary supports abundant wild oyster populations, ongoing monitoring of oyster populations is required to ensure that appropriate management strategies are established to ensure the persistence of this important component of the ecosystem. Our sampling of two key oyster habitats provides an important baseline against which future studies can assess change.